2021
DOI: 10.17219/acem/138962
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients and internal medicine patients attitude towards COVID-19 vaccination in Poland

Abstract: Background. The initial approval of the Pfizer/BioNTech and Moderna vaccines by the European Medicines Agency (EMA) and Food and Drug Administration (FDA) marked a milestone in the fight against the COVID-19 pandemic. The increased public debate about the vaccine development process and vaccine side effects has activated the anti-vaccine community, which has begun to spread conspiracy theories about vaccine safety. Objectives.Our study is the first to investigate the awareness of Polish patients suffering from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Variables specific to Eastern Europe that predict the willingness to vaccinate have also been highlighted. Several studies explored the hesitancy toward COVID-19 vaccination in Eastern European populations with comorbidities or pregnancy [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Variables specific to Eastern Europe that predict the willingness to vaccinate have also been highlighted. Several studies explored the hesitancy toward COVID-19 vaccination in Eastern European populations with comorbidities or pregnancy [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…All stakeholder groups reported barriers to COVID‐19 vaccination uptake in this population, supporting the previous research. Barriers included lack of confidence in science and vaccine efficacy, 16 , 19 , 21 , 23 , 24 fear of side effects, 16 , 21 , 22 , 23 , 24 , 25 , 26 , 30 belief that COVID‐19 is benign, 16 , 23 , 25 and concern about vaccine impact on treatment. 18 , 22 , 26 Notably, most hesitation related to the lack of information about vaccine efficacy and impacts within the cancer context, rather than general antivaccination sentiment.…”
Section: Discussionmentioning
confidence: 99%
“…International research has reported that while the majority of cancer patients intended to be vaccinated as soon as the COVID‐19 vaccine was available, there were still a proportion who were undecided or hesitant about vaccination. 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 The research indicates that cancer patients who are female, 20 , 21 , 23 , 27 , 29 , 30 younger in age, 20 , 21 , 23 , 24 , 27 , 30 less educated/health literate, 19 , 23 , 24 , 26 , 27 , 29 , 30 have worse health status, 20 , 22 and are non‐white 21 , 27 , 29 are more likely to be hesitant. Commonly reported barriers to vaccine uptake include lack of confidence in science and vaccine efficacy, 16 , 19 , 21 , 23 , 24 fear of side effects, 16 , 21 , 22 , 23 , 24 , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By knowing the actual reasons behind not reaching the country’s vaccination target, specific measures can be taken to increase people’s confidence and compliance. For instance, cardiovascular patients within our 194-sized sample did not have higher vaccination rates, although cardiovascular diseases are known risk factors for developing severe forms of COVID-19 [ 33 , 34 , 35 , 36 ]. However, the presence of diabetes was significantly associated with a better score in our questionnaire and with a higher proportion of vaccinated people.…”
Section: Discussionmentioning
confidence: 99%